The Effects of Family Firm Specific Sources of TMT Diversity: The Moderating Role of Information Exchange Frequency - Ling, Yan; Kellermanns, Franz W. (Journal of Management Studies, 2010)
abstractWe examine the relationships among three family firm specific sources of top management team (TMT) diversity (the generation in charge of the family firm, the number of family employees, and the number of employed generations) and family firm performance. By integrating upper‐echelons and team process research, we hypothesize that these TMT diversity sources interact with information exchange frequency among TMT members to affect family firm performance. Multisource survey data with lagged performance measurement, including CEOs and TMT members from 86 family firms, support our hypotheses. We discuss the implications of our findings and develop avenues for future research.